The Role of Workplace Spirituality (WPS) in Enhancing Job Performance: Evidence from Public Sector Universities - Anila Ali; Dr. Uzma Shahzadi; Dr. Asma Khizar (Policy Journal of Social Science Review, 2026)
The study was intended to examine the relationship between Workplace Spirituality (WPS) and job performance of university teachers. A correlational research design was used. The study participants were teachers of public sector universities in Punjab, Pakistan. The study included a sample of 121 teachers from 6 public sector universities: University of Sargodha, Government College University Faisalabad, Bahauddin Zakariya University Multan, The Islamia University of Bahawalpur, Fatima Jinnah Women University Rawalpindi and University of Gujrat. Four departments from faculty of social sciences of each university were purposively selected and the50% respondents from each department were randomly selected as participants for data collection. Data was collected from participants by using an adapted WPS Scale and a Job Performance Scale. Data was analyzed through descriptive statistics, such as frequency, mean, standard deviation, t-tests and Pearson correlation to examine relationships between focal variables of the study. The results showed a significant positive relationship between WPS and job performance of university teachers. It is recommended that University administrators and department heads are encouraged to create a positive, ethical and value-driven workplace to strengthen teachers' sense of meaning, connection and being aligned with organizational values, which will support overall job performance of teachers. Keywords: Workplace Spirituality, Job Performance, Public Sector Universities, University Teachers